INHERITANCE OF EARLY ARCHAEAN PB-ISOTOPE VARIABILITY FROM LONG-LIVED HADEAN PROTOCRUST - Kamber B.S.; Collerson K.D.; Moorbath S.; Whitehouse M.J. (My University, 2003)
Comparison of initial Pb-isotope signatures of several early Archaean (3.65–3.82 Ga) lithologies (orthogneisses and metasediments) and minerals (feldspar and galena) documents the existence of substantial isotopic heterogeneity in the early Archaean, particularly in the 207Pb/204Pb ratio. The magnitude of isotopic variability at 3.82–3.65 Ga requires source separation between 4.3 and 4.1 Ga, depending on the extent of U/Pb fractionation possible in the early Earth. The isotopic heterogeneity could reflect the coexistence of enriched and depleted mantle domains or the separation of a terrestrial protocrust with a 238U/204Pb (µ) that was ca. 20–30% higher than coeval mantle. We prefer this latter explanation because the high-µ signature is most evident in metasediments (that formed at the Earth's surface). This interpretation is strengthened by the fact that no straightforward mantle model can be constructed for these high-µ lithologies without violating bulk silicate Earth constraints. The Pb-isotope evidence for a long-lived protocrust complements similar Hf-isotope data from the Earth's oldest zircons, which also require an origin from an enriched (low Lu/Hf) environment. A model is developed in which ≥3.8-Ga tonalite and monzodiorite gneiss precursors (for one of which we provide zircon U-Pb data) are not mantle-derived but formed by remelting or differentiation of ancient (ca. 4.3 Ga) basaltic crust which had evolved with a higher U/Pb ratio than coeval mantle in the absence of the subduction process. With the initiation of terrestrial subduction at, we propose, ca. 3.75 Ga, most of the ≥3.8-Ga basaltic shell (and its differentiation products) was recycled into the mantle, because of the lack of a stabilising mantle lithosphere. We argue that the key event for preservation of all ≥3.8-Ga terrestrial crust was the intrusion of voluminous granitoids immediately after establishment of global subduction because of complementary creation of a lithospheric keel. Furthermore, we argue that preservation of ≥3.8-Ga material (in situ rocks and zircons) globally is restricted to cratons with a high U/Pb source character (North Atlantic, Slave, Zimbabwe, Yilgarn, and Wyoming), and that the Pb-isotope systematics of these provinces are ultimately explained by reworking of material that was derived from ca. 4.3 Ga (i.e. Hadean) basaltic crust.
Keywords: Precambrian::Archean; Докембрий::Архей